ATHEROSCLEROSIS: HOW TO START UP A "COUNT DOWN" CLOCK? WE DON'T KNOW, WE CAN NOT OR WE DO NOT WANT? - L. N. Malay (Рациональная фармакотерапия в кардиологии)
Clinical cases of long-term use of rosuvastatin are presented with an estimation of its effect on the soft end (lipid profile) and hard end (number of heart attacks, strokes, heart failure, hospitalization for cardiovascular causes) points are given. The results of studies on rosuvastatin (ASTEROID, CORONA, METEOR, ORION, COSMOS) are presented. Clinical guidelines on the management of patients with stable ischemic heart disease are considered on the example of COURAGE trial.